Implementasi Nilai Nekaf Mese Ansaof Mese Dalam Dialog Antarbudaya Dan Identitas - Costa, Francisco da; Silva, Augusto Almeida da; Turkel, Ajito Abel Anjos; da Silva, Arjito; Lasi, Bartolomeo do Santos; Marçal, Cristalino da Costa; Pereira, Tunito; Senda, Siprianus Soleman; Subani, Yohanes; Naif, Oktovianus (Metta : Jurnal Ilmu Multidisiplin, 2025)
The Atoin Meto community communally has a philosophy of life that serves as the foundation of their lives, which is known as nekaf mese asnaof mese. The philosophy of life is oriented towards the facilitation of cultural exchange and the consolidation of collective identity. Therefore, the objective of this study is to examine the manner in which the life philosophy of nekaf mese ansaof mese is employed to enhance cultural relations and the identity of the Atoin Meto in the Sacato-Wini region. This study used a qualitative method with a literature approach and in-depth interviews. The results indicated that the value of nekaf mese ansaof mese is internalized through social practices such as gotong royong (hena loak), customary deliberation (nifuni), and cultural rituals (el'ana, ela'naek, pah banu). These practices foster solidarity, peaceful conflict resolution, and reconciliation among diverse identities. Furthermore, this value serves to reinforce the spiritual connection that exists between humans, nature, and the Transcendent. Consequently, Nekaf Mese Ansaof Mese is instrumental in fostering inclusive intercultural relations and fortifying local and national identities in the context of globalization and the challenges posed by modernity.